COMMUNICATION PSYCHOLOGY IN FOSTERING THE DISCIPLINE OF MAHASANTRI AT MA’HAD AL-JAMI’AH UIN RADEN INTAN LAMPUNG - Azizah Azzahra Jaenuri; M. Nasor; Khairullah Khairullah (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2026)
This study aims to analyse the implementation of communication psychology in fostering time discipline among mahasantri at Ma’had al-Jami’ah UIN Raden Intan Lampung. The study employed a qualitative approach using a case study design. The research informants consisted of five Ma’had administrators and eight mahasantri selected purposively. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, encompassing data reduction, data display, thematic coding, and conclusion drawing. The findings reveal that empathetic, dialogical, and interpersonal communication approaches are more effective in cultivating disciplinary awareness than authoritarian approaches. Furthermore, the study identifies a disciplinary development model based on a balanced combination of psychological and structural approaches, implemented through empathy, mentoring, regulations, and sanctions. These findings reinforce the discourse of communication psychology in character development within higher education Ma’had environments.